2016
DOI: 10.1021/acs.nanolett.6b03378
|View full text |Cite
|
Sign up to set email alerts
|

Nanodiamond–Gadolinium(III) Aggregates for Tracking Cancer Growth In Vivo at High Field

Abstract: The ability to track labeled cancer cells in vivo would allow researchers to study their distribution, growth, and metastatic potential within the intact organism. Magnetic resonance (MR) imaging is invaluable for tracking cancer cells in vivo as it benefits from high spatial resolution and the absence of ionizing radiation. However, many MR contrast agents (CAs) required to label cells either do not significantly accumulate in cells or are not biologically compatible for translational studies. We have develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
84
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 67 publications
(85 citation statements)
references
References 57 publications
1
84
0
Order By: Relevance
“…In fact, this concentration-dependent shift in contrast was further analyzed by relaxation time in comparison to healthy tissue, and from this data a model was developed which was used to predict tumor morphology and cellular architecture at day 26 based on MR images alone. This model, which was verified in this study by comparison with histology, can be used in future studies to monitor growth dynamics and morphological changes during tumor progression [180]. Furthermore, ND-Gd labeling was noted to have no noticeable effect on cell growth or differentiation, and biodistribution studies after 26 days concluded that 95% of ND-Gd remained within the labeled cells throughout the entire duration of the study.…”
Section: Bioimagingsupporting
confidence: 63%
See 1 more Smart Citation
“…In fact, this concentration-dependent shift in contrast was further analyzed by relaxation time in comparison to healthy tissue, and from this data a model was developed which was used to predict tumor morphology and cellular architecture at day 26 based on MR images alone. This model, which was verified in this study by comparison with histology, can be used in future studies to monitor growth dynamics and morphological changes during tumor progression [180]. Furthermore, ND-Gd labeling was noted to have no noticeable effect on cell growth or differentiation, and biodistribution studies after 26 days concluded that 95% of ND-Gd remained within the labeled cells throughout the entire duration of the study.…”
Section: Bioimagingsupporting
confidence: 63%
“…By conjugating paramagnetic ions to NDs, their relaxivity is improved due to the increased interaction of the ions with water of the solvent phase present on the ND surface. To demonstrate this concept, Gd(III) chelates were chemically conjugated with amino-functionalized NDs by carbodiimide crosslinking to form ND-Gd aggregates [180]. ND-Gd displayed a 10-fold increase in relaxivity with respect to unmodified Gd.…”
Section: Bioimagingmentioning
confidence: 99%
“…e) A high‐field magnetic resonance imaging (MRI) of cells labeled with nanodiamond–gadolinium (III) aggregates (NDG). Reproduced with permission . Copyright 2016, American Chemical Society.…”
Section: Labelingmentioning
confidence: 99%
“…T 2 contrast can be achieved via metallic impurities in the diamond material . Recently, Meade and co‐workers conjugated gadolinium (III) (Gd(III)) to the surface of NDs for improving MR imaging . NDs enhance T 1 and T 2 contrast, while Gd(III) is typically effective for T 1 positive contrast .…”
Section: Labelingmentioning
confidence: 99%
“…4045 This synthetic strategy consisted of covalently attaching Gd(III) complexes to thiol-modified oligonucleotides (via click chemistry) and conjugating this derivative to 13.1 nm gold nanoparticles (AuNPs). 5,42 Because of the increased local concentration of Gd(III) per particle, there is a significant increase in the observed r 1 (relaxivity mM −1 s −1 , particularly at low magnetic field strengths).…”
mentioning
confidence: 99%